1984
DOI: 10.1007/bf00432038
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic-induced striatal dopamine receptor supersensitivity in mice: Relationship to dose and drug

Abstract: Clozapine and molindone administered to mice for 21 days did not elevate the density of striatal 3H-spiperone binding sites at doses clinically equivalent to 1.5 mg/kg haloperidol, which elevated binding by 29%. Thioridazine (25 mg/kg) elevated binding by 25%. It appears that clinically equivalent doses of clozapine and molindone have reduced ability to induce striatal D-2 dopamine receptor supersensitivity. These data are discussed in relationship to in vitro potencies and toxicity. The dose-response relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…7). The fact that acute and long-term haloperidol treatments did not significantly change the responsiveness of accumbens neurons to DA could appear most intriguing, given the well-documented supersensitivity of dopaminergic receptors after longterm neuroleptic treatments (Burt et al, 1977;Muller and Seeman, 1978;Skirboll and Bunney, 1979;Severson et al, 1984). However, several studies have reported that, contrary to microiontophoretic applications of haloperidol which antagonize DA-induced inhibition of caudate or accumbens neurons (Akaike et al, 1983(Akaike et al, , 1984, systemic administration of neuroleptics is ineffective in blocking the effects of microiontophoretic applications of DA (Ben-At-i and Kelly, 1976;Somjen et al, 1976;Zarzecki et al, 1977;Skirboll and Bunney, 1979;Johnson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…7). The fact that acute and long-term haloperidol treatments did not significantly change the responsiveness of accumbens neurons to DA could appear most intriguing, given the well-documented supersensitivity of dopaminergic receptors after longterm neuroleptic treatments (Burt et al, 1977;Muller and Seeman, 1978;Skirboll and Bunney, 1979;Severson et al, 1984). However, several studies have reported that, contrary to microiontophoretic applications of haloperidol which antagonize DA-induced inhibition of caudate or accumbens neurons (Akaike et al, 1983(Akaike et al, , 1984, systemic administration of neuroleptics is ineffective in blocking the effects of microiontophoretic applications of DA (Ben-At-i and Kelly, 1976;Somjen et al, 1976;Zarzecki et al, 1977;Skirboll and Bunney, 1979;Johnson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Work in animal models shows that at equivalent doses and modes of treatment, long-term exposure to haloperidol produces dopamine receptor supersensitivity, while exposure to olanzapine or ziprasidone does not [10,12,156,175,176,177]. The two classes of antipsychotics have common but also different pharmacological properties.…”
Section: Choice Of the Antipsychoticmentioning
confidence: 99%
“…Overall, it appears that the chronic treatment of rats with CLOZ does not significantlyaltertheB,,,andKDofD2receptorsintherat striatum (Boysonetal., 1988;Jiangetal., 1990;Kusumietal., 1995;Lee and Tang, 1984;O'Dell et al, 1990;Rupniak et al, 1985;Seeget et al, 1982;Severson et al, 1984). A recent study has also shown that chronic CLOZ administration does not alter the density of striatal Dz receptors in mice (Zhang et al, 1995).…”
Section: Effect Of Chronic Cloz Administration On D Receptors In Thementioning
confidence: 86%